The Synthesis and Application of 2-Cyano and -Ester Containing Anilines: Selective Copper-Catalyzed Reductive Amination, N-Benzylation, and Cyclization Reactions - Huang, Ziwei; Lin, Zirui; Mai, Jiexiong; Lv, Shaohuan; Xie, Feng; Yuan, Youxue; Zhang, Wenbing; Qian, Fan; Li, Bin (Synthesis, 2022)
A convenient and practical pathway to 2-cyano and 2-ester anilines is described via efficient and selective copper(II)-catalyzed reductive amination via hydrosilylation process. Both 2-cyano and 2-ester anilines were successfully synthesized with good functional group tolerance and high selectivity. The application of the 2-cyano and -iodine containing anilines was developed in the synthesis of indoloindole derivatives via CuSO4-catalyzed N-benzylation and cyclization reaction in ‘one pot’. More interestingly, the photophysical property investigations of these 2-cyano and 2-ester containing anilines exhibit excellent fluorescent properties, which have great potential application in the development of interesting near-ultraviolet optical devices in the near future.
Keywords: copper catalysis; hydrosilane; reductive amination; amines; indoloindole